Social Demand for Ecosystem Services Provided by Peri-Urban Forests: the Case Study of the Tlemcen Forest (Algeria) - Fadila, Larabi; Mohamed, Berrichi; Alessandro, Paletto (Journal of Environmental Accounting and Management, 2026)
Recently, many studies have highlighted the role of urban and peri-urban forests in mitigating environmental pollution and maintaining human quality of life by integrating the concepts of ecosystem services into forest management strategy. To increase the social acceptance and to reduce the conflicts between users, citizens’ preferences towards ecosystem services should be included in the decision-making process. In the present study, a structured questionnaire was administered to a sample of 180 citizens and 50 forest managers of the Tlemcen peri-urban forest (Algeria). The collected data was processed to show convergent and different preferences between forest managers and citizens towards the main categories of ecosystem services – provisioning, regulating, supporting, and cultural services – provided by the Tlemcen peri-urban forest. The results show that for both groups of respondents the three most important ecosystem services are: tourism and recreation (cultural services), soil erosion protection (regulating services), and biodiversity conservation (supporting services). Conversely, provisioning services (wood and non-wood forest products) are considered marginal by the two groups of respondents. These results are in line with international literature, which highlights in post-modern society an increase in importance of intrinsic values of nature at the expense of instrumental values.